Characterization and Stability Test of Hydrolyzed Collagen Glyserosomes - Safiul Fitria, Nur Indah; Erawati, Tristiana; Miatmoko, Andang; Soeratri, Widji (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Hydrolyzed collagen is a protein obtained from enzymatic denaturation of collagen with a molecular weight of about 10 kDa, and it has been reported to produce anti-aging properties. Delivering hydrolyzed collagen into the dermis becomes a great challenge due to its large molecular weight, so glycerosome, a deformable vesicle containing glycerol as the edge activator, was developed to carry it into the dermis layer. Objective: The study aimed to determine the effect of increasing the concentration of glycerol and hydrolyzed collagen on the characteristics and stability of hydrolyzed collagen glycerosomes. Methods: Glycerosomes were composed of soy lecithin and prepared using a thin film lipid method. The lipid film was hydrated with phosphate-buffered saline pH 5 containing different glycerol concentrations (20% and 40%) and hydrolyzed collagen (2.5% and 5%). Then, characteristic tests and stability tests were carried out. Results: Hydrolyzed collagen glycerosomes had vesicle sizes of 170-180 nm, polydispersity index of 0.253-0.279, zeta potential values of -23.70 to -26.50 mV with deformability indexes of 2.25-3.49. The highest percentage of entrapment efficiency was 85.72%, achieved with a glycerol concentration of 40%. During the stability test at 25°C for 12 weeks, the hydrolyzed collagen glycerosomes did not experience pH and entrapment efficiency changes, but it increased the vesicle size. Conclusion: The use of 40% glycerol produced more deformable vesicles than 20% glycerol in hydrolyzed collagen glycerosomes; however, a formula improvement is required to improve the stability of glycerosomes.